Evaluation of Rifampicin Resistance in Tuberculosis Patients Co-Infected with HIV/AIDS in Port-Harcourt, Nigeria - Atemie, Kennedy Tamunokubie; Udujih, Helen Ifeoma; Nwosu, Dennis Chimezie; Ndubueze, Chizaram Winners; Lawson, Danagogo Stephenson (British Journal of Healthcare and Medical Research, 2024)
Due to insufficient information on the prevalence of rifampicin resistance among people co-infected with TB and HIV/AIDS, this study was aimed at determining the prevalence of rifampicin resistance in HIV/AIDS and tuberculosis (TB) patients attending clinical appointments at the University of Port Harcourt Teaching Hospital (UPTH), Rivers State, Nigeria. A total of 3768 patients, comprising 1906 (58.6%) females and 1862 (49.4%) males, were enrolled in the study. Serial testing algorithms (rapid diagnostic kits) and Genexpert were used to screen for HIV and TB, respectively. The TB result showed that a total of 305 (8.1%), with men being 175 (57.4%) and women being 130 (42.6%), tested positive. Also, 32 patients (0.8%) had HIV and TB co-infections. Among those positive for TB, 11 (3.6%), including 5 (1.6%) men and 6 (2.0%) women, were rifampicin-resistant positive. Of the 32 patients with MTB/HIV co-infection, 3 (9.4%) were rifampicin-resistant, 20 (62.5%) were sensitive, and 9 (28.1%) were indeterminate. Furthermore, of the 32 MTB/HIV co-infected individuals, 27 (84.4%) had HIV 1 mono-infection, none had HIV 2 mono-infection, and 5 (15.6%) had HIV 1 and HIV 2 co-infection. The co-infected patients with HIV 1 and HIV 2 showed signs of rifampicin-resistant tuberculosis (RR-TB). These outcomes suggest that MTB transmission among the populace is linked to co-infection with HIV 1 and HIV 2, as well as rifampicin resistance in TB patients. Therefore, to properly manage both infections and lessen their impact, HIV testing among patients getting MTB treatment is highly encouraged.